A Review on Cloud Computing, It’s Overview and Current Research Challenges - Dayanand; Kumari, Ragini; Patrick, Anubhav; Pathak, Disha Mohini (International Journal of Computer Sciences and Engineering, 2019)
Cloud computing is an emerging computing technology and trend in research field today. It is an internet based computing model that shares pool of computing resources such as servers, storage, computer networks, applications and services to other devices on demand over a network on a leased basis. Many industries such as banking, healthcare and education are moving towards cloud due to efficiency of services provided by the pay per use pattern based on resources such as processing power used, transactions carried out, bandwidth consumed, data transferred or storage space occupied. Cloud computing is aimed at providing IT as a service to the cloud users on demand basis with greater flexibility, availability, reliability and scalability. There are various issues such as load balancing, management of energy, privacy and security which hinders their growth. Serverless architecture, Security and load balancing are critical issues in cloud computing in present era. This paper presents review on use of cloud computing, its various models, cloud computing architecture and various research challenges in cloud computing.